Characterisation Of Hydroxyapatite Coated And Uncoated Titanium And Effects Towards Saos-2 Cells - Hamid, Mohammad Idham Abd (2024)
Titanium and its alloys have been recently emphasised as potential biocompatible metals due to their good mechanical properties such as being low density but stronger, withstanding strain during internal fixation and having good durability. This study focused more on the biocompatibility study. In this study, uncoated and hydroxyapatite (HA) coated samples were used. HA-coated samples were prepared by coating HA onto a titanium alloy (Ti6Al4V) using the solvent casting method. The uncoated samples were prepared by grinding and polishing the Ti6Al4V samples. First characterisation was performed using Field Emission Scanning Electron Microscope (FESEM) on both types of samples. X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR) analyses were conducted with the coating of HA-coated samples. The biocompatibility of the samples was evaluated using Saos-2 cells using MTT, LDH and Sircol collagen assay. On FESEM characterisation, the coating of HA onto Ti6Al4V, achieved through the solvent casting method, led to irregularities in the morphological surface characteristics compared to uncoated Ti6Al4V. Analysis using X-ray Diffraction (XRD) demonstrated the presence of crystalline phase in the HA-coated Ti6Al4V. Fourier Transform Infrared (FTIR) analysis indicated the presence of phosphate and carbon organic compounds on the surface of HA-coated Ti6Al4V. A positive cell response to the titanium ions was revealed during the first 7 days of the biocompatibility study using the indirect method such as MTT, LDH and Sircol collagen assay.